Mosquitoes of the world - Wilkerson, Richard C., 1946- (Johns Hopkins University Press, 2021)
"In this two-volume set, three of the world's leading experts on the topics of mosquito disease, ecology, and systematics have created the definitive reference work on the family Culicidae. This book provides an overview of the biology, evolution, and ecology of mosquitoes and then supplies genus-by-genus accounts with close-up images. This is a unique reference work for entomologists, public health professionals, and reference libraries"--